On the integration of product and process models in engineering design. (21st March 2017) - Eckert, Claudia M.; Wynn, David C.; Maier, Jakob F.; Albers, Albert; Bursac, Nikola; Xin Chen, Hilario L.; Clarkson, P. John; Gericke, Kilian; Gladysz, Bartosz; Shapiro, Daniel
Abstract : Models of products and design processes are key to interacting with engineering designs and managing the processes by which they are developed. In practice, companies maintain networks of many interrelated models which need to be synthesised in the minds of their users when considering issues that cut across them. This article considers how information from product and design process models can be integrated with a view to help manage these complex interrelationships. A framework highlighting key issues surrounding model integration is introduced and terminology for describing these issues is developed. To illustrate the framework and terminology, selected modelling approaches that integrate product and process information are discussed and organised according to their levels and forms of integration. Opportunities for further work to advance integrated modelling in engineering design research and practice are discussed.